Learner engagment in L2 writing - Anna Martinović (ExELL (Explorations in English Language and Linguistics))
One of the most current themes in second language (L2) learning is learner engagement. This broad construct entails several elements including behavioural, emotional, and cognitive engagement. The aim of this study was to investigate learner engagement in a writing course among English L2 university students, and engagement with feedback. The quantitative data showed moderately high levels of learner engagement across all the engagement dimensions. Differences between dimensions of engagement and grades were not found. Qualitative analyses showed a dominance of positive emotions, including interest, curiosity, and optimism. Behavioural engagement was tied to intrinsic and extrinsic reasons, suggesting the importance of motivation for learner engagement. Feedback encouraged students to use meta-cognitive and cognitive strategies, helping them focus on specific language forms.